European defence cooperation after the Lisbon treaty: The road is paved for increased momentum - Christine Nissen (Danish Institute for International Studies (DIIS), 2015)
This report takes stock of the changes made to the European Security and Defence Policy since the adoption of the Lisbon Treaty in 2009. The report also examines what impact such changes have on Denmark, and specifically whether the Danish opt-out from EU defence cooperation will have increased consequences after the implementation of the Lisbon Treaty changes. By examining the Lisbon Treaty changes to the CSDP, and assessing how these affect Danish security and defence policy, the report provides an updated state of the art of the current reality for European defence cooperation after the Lisbon Treaty and where Denmark fits into this cooperation. The report concludes that the changes brought about by the Lisbon Treaty provide for increased consistency and coherence of policies and instruments due to the new foreign policy system of an empowered High Representative of the Union for Foreign Affairs and Security Policy and the creation of the European External Action Service. Moreover, specific provisions to the CSDP pave the way for more ambitious arrangements between the member states, ultimately leading to a more assertive CSDP. In a post-Lisbon context there are signs that the new EU actors and member states are pushing for strengthened EU defence cooperation. However, several of the Lisbon provisions have not yet been fully realised in practice and for Denmark, this means that the opt-out has not been more frequently invoked in a post-Lisbon context. There are, however, indications that the Danish opt-out may have increased consequences for Denmark, including that Denmark will remain excluded from important aspects of European defence cooperation, especially in relation to the intensified use of a 'comprehensive approach' to EU cooperation on defence, current projects on developing common capabilities, and within the ongoing process of strengthening the European defence industry.
Keywords: 300